Estudio de la depreciación de los activos fijos y su efecto en el costo de producción - rentabilidad, en las empresas del sector textil en el Perú, año 2016 - Vásquez Machuca, Segundo Norbi (2017)
ABSTRACT The present thesis entitled STUDY OF THE DEPRECIATION OF FIXED ASSETS AND THEIR EFFECT ON THE COST OF PRODUCTION - PROFITABILITY, IN THE COMPANIES OF THE TEXTILE SECTOR IN PERU, YEAR 2016. Is a work that deals with the research of one of the main factors that affect the Production Costs of the manufacturing companies of the textile sector, which is the Depreciation, as an expense that results from the use of machinery during the production process The purpose of the research is to determine which of the methods currently applied from the accounting point of view contributes to a more adequate determination the cost of the product in order to determine the margin of profit and therefore the selling price, With the purpose of being able to compete in the national and international market. The research was carried out through the various economic information disseminated by the various entities of the public sector, and private entities, linked to the textile sector. The same ones that report on the decrease of the textile production, for many years, mainly due to the importation of textiles from foreign markets, mainly from China, whose prices are below the national market. Likewise, various sources of internet and bibliographic information have been used on the subject. In the present research, have made possible to determine, through a comparative study of depreciation methods, that the most appropriate method to be applied to the fixed assets of the production area is the Depreciation Method of Service. Working hours, which determines a more reasonable depreciation value, and which will be added to the cost of manufacturing the textile products. Depreciation that directly affects the Cost of Production, Cost of Sale, Profitability and Sale Price. Element that constitutes the final value of the products, and that will be the determining factor in the economic growth of the company, within a framework of competition in the national and international market.